South Korea's Interests in THAAD Development Cooperation with the United States - Maulidiyah Dewi Sejati; Indrawati Indrawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Security is one of the main focuses of countries in the world. In achieving this, many countries cooperate or join alliances. South Korea has long joined the United States alliance because North Korea has weapons of destruction, which is the biggest threat to South Korea. One of the commitments the United States gives to its allies is to protect defence and security. When North Korea conducted its fourth nuclear test in January 2016, South Korea and the United States worked together to build the Terminal High Altitude Area Defense (THAAD) in Seongju, South Korea. This research analyzes what interests South Korea wants to achieve in security cooperation with the United States. The theory of national interest and the concept of security dilemma is used to answer this problem. This research was arranged systematically using qualitative research methods. The research results show that South Korea's interests in THAAD development cooperation with the United States include 1)strengthening alliances with the United States, 2)North Korea's fourth nuclear test, which led to an imbalance of military power, and 3)the emergence of China as a threat to South Korea.